Association between erythritol and lung cancer: a two-sample Mendelian randomization study - Yongsheng Zhao; Renyan Zheng; Kexin Luo; Haiyang Zhao; Wanping Xiang (Nutrition & Metabolism)
Abstract Background Sweeteners have been widely added to food and beverages due to their low-calorie and sweetening properties. However, the role of sweeteners in cancer risk has been a subject of extensive debate over the past few decades. Objective We aimed to elucidate the causation between the commonly used natural sweetener erythritol and the risk of lung cancer (LC) using Mendelian randomization (MR). Methods Data on erythritol and its metabolites were obtained from publicly available genome-wide association studies data. Summary data on LC and its subtypes were obtained from a large-scale genetic study conducted by the Transdisciplinary Research of Cancer in Lung of the International Lung Cancer Consortium and the Lung Cancer Cohort Consortium. We conducted independent two-sample MR analyses to assess the causation between erythritol and LC and its subtypes. Results The inverse variance weighted method of MR analysis showed no evidence supporting causation between erythritol and LC or its histological subtypes. Sensitivity analysis further supported the results. Conclusion Our study findings do not support genetic association between erythritol and LC or its subtypes.